Perancangan Aplikasi Sistem Informasi Pengelolaan Barang Inventaris Berbasis Android - Budi Hartanto; Eva Itma Anna; Rully Nanang Septiawan (Universitas Mitra Indonesia, 2021)
AbstractIn processing office inventory mutation data at the Mesuji Sekampung River Basin Center, the office inventory data management system is still manual in the form of bookkeeping, besides that there is also no computerized system in processing office inventory data so that an application is needed that can facilitate and assist a job. in processing office inventory mutation data. To overcome this problem, one solution to overcome this is to build a system that can facilitate and assist a job in processing office inventory mutation data at the Mesuji Sekampung River Basin Center to handle this problem. Therefore, the author proposes an Android-based Office Inventory Data Processing Information System at the Great Hall of the Mesuji River Basin Sekampung. The results of this study are the information system for processing Inventory Data at the Central Mesuji Sekampung River Basin which has been developed to facilitate sub-sections in the process of processing inventory data as well as collecting and searching inventory data easily and quickly and sub-sections can find out what assets are owned.